Novel retrotransposon analysis reveals multiple mobility pathways dictated by hosts - Ichiyanagi, Kenji; Nakajima, Ryo; Kajikawa, Masaki; Okada, Norihiro (Genome Research, 2007)
Autonomous non-long-terminal-repeat retrotransposons (NLRs) proliferate by retrotransposition via coordinated reactions of target DNA cleavage and reverse transcription by a mechanism called target-primed reverse transcription (TPRT). Whereas this mechanism guarantees the covalent attachment of the NLR and its target site at the 3′ junction, mechanisms for the joining at the 5′ junction have been conjectural. To better understand the retrotransposition pathways, we analyzed target–NLR junctions of zebrafish NLRs with a new method of identifying genomic copies that reside within other transposons, termed “target analysis of nested transposons” (TANT). Application of the TANT method revealed various features of the zebrafish NLR integrants; for example, half of the integrants carry extra nucleotides at the 5′ junction, which is in stark contrast to the major human NLR, LINE-1. Interestingly, in a cell culture assay, retrotransposition of the zebrafish NLR in heterologous human cells did not bear extra 5′ nucleotides, indicating that the choice of the 5′ joining pathway is affected by the host. Our results suggest that several pathways exist for NLR retrotransposition and argue in favor of host protein involvement. With genomic sequence information accumulating exponentially, our data demonstrate the general applicability of the TANT method for the analysis of a wide variety of retrotransposons.